Two new rove beetle genera in Staphylininae that reduce “Heterothops” and “Quedius” taxonomic wastebaskets (Coleoptera, Staphylinidae) - José L. Reyes-Hernández; Alexey Solodovnikov (ZooKeys)
The here-provided description of the new genera Chiquiticus gen. nov. and Nitidocolpus gen. nov. was necessitated by a phylogenetic study of Staphylininae (to be published separately), which will be used for the proper characterization of their respective new suprageneric lineages in an upcoming update of the higher classification of this subfamily. Both new genera are erected for species that had been previously described but misplaced in the highly polyphyletic “taxonomic wastebasket” genera Heterothops (Amblyopinina) and Quedius (Quediina), resulting in the following new combinations: Chiquiticus arizonicus (Smetana, 1971), comb. nov. ex. Heterothops; Chiquiticus campbelli (Smetana, 1971), comb. nov. ex. Heterothops; †Chiquiticus cornelli (Chatzimanolis & Engel, 2013), comb. nov. ex. Heterothops; Chiquiticus gemellus (Smetana, 1971), comb. nov. ex. Heterothops; †Chiquiticus infernalis (Chatzimanolis & Engel, 2013), comb. nov. ex. Heterothops; Chiquiticus occidentis (Casey, 1886), comb. nov. ex. Heterothops; Chiquiticus pusio (LeConte, J. L., 1863), comb. nov. ex. Heterothops; Chiquiticus rambouseki (Blackwelder, 1943), comb. nov. ex. Heterothops; Nitidocolpus aurofasciatus (Bernhauer, 1917), comb. nov. ex. Quedius; Nitidocolpus championi (Sharp, 1884), comb. nov. ex. Quedius; Nitidocolpus columbinus (Bernhauer, 1917), comb. nov. ex. Quedius; Nitidocolpus germaini (Bernhauer, 1917), comb. nov. ex. Quedius; Nitidocolpus illatus (Sharp, 1884), comb. nov. ex. Quedius; Nitidocolpus laeticulus (Sharp, 1884), comb. nov. ex. Quedius; Nitidocolpus triangulum (Fauvel, 1891), comb. nov. ex. Quedius. Additionally, several more Neotropical Quedius species, which resemble Nitidocolpus, have been revised and transferred to the amblyopinine genus Cheilocolpus or the cyrtoquediine genus Cyrtoquedius, with the following new combinations: Cheilocolpus forsteri (Scheerpeltz, 1960), comb. nov. ex. Quedius; Cheilocolpus speciosus (Bernhauer, 1917), comb. nov. ex. Quedius; Cheilocolpus viridulus (Erichson, 1840), comb. nov. ex. Quedius; Cyrtoquedius viridipennis (Fauvel, 1891), comb. nov. ex. Quedius. The undescribed species diversity of the newly described genera is also highlighted.